2022
DOI: 10.1002/ccr3.6772
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Guillain–Barre syndrome in the SARS‐CoV‐2 era: Is there any causative relation?

Abstract: We reported an association between SARS‐CoV‐2 infection and Guillain–Barre syndrome (GBS). From 37 patients with GBS, previous SARS‐CoV‐2 clinical clues, including fever, cough, and diarrhea, were recorded in 18 patients. Among them, SARS‐CoV‐2 IgG was detected in seven patients, considered confirmed as cases. SARS‐CoV‐2 PCR was positive in just one patient. Although we found no increase in patient recruitment during the pandemic compared to previous years, our study indicated that SARS‐CoV‐2 is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…To the Editor, We read with interest the article by Pourbahtyaran et al about a prospective study on seven pediatric patients with SARS-CoV-2-associated Guillain Barre syndrome (GBS) recruited between March 2020 and August 2021 in a single Iranian center. 1 These patients were compared with 15 GBS patients who were negative for SARS-CoV-2 mRNA as well as antibodies recruited during the same period. 1 It was found that the prevalence of GBS did not increase during the pandemic compared with previous years but that the outcome of SARS-CoV-2-related GBS was worse compared with non-COVID-related GBS.…”
Section: Sars-cov-2-related Polyradiculitis Must Be Preceded By Pcr-c...mentioning
confidence: 99%
See 4 more Smart Citations
“…To the Editor, We read with interest the article by Pourbahtyaran et al about a prospective study on seven pediatric patients with SARS-CoV-2-associated Guillain Barre syndrome (GBS) recruited between March 2020 and August 2021 in a single Iranian center. 1 These patients were compared with 15 GBS patients who were negative for SARS-CoV-2 mRNA as well as antibodies recruited during the same period. 1 It was found that the prevalence of GBS did not increase during the pandemic compared with previous years but that the outcome of SARS-CoV-2-related GBS was worse compared with non-COVID-related GBS.…”
Section: Sars-cov-2-related Polyradiculitis Must Be Preceded By Pcr-c...mentioning
confidence: 99%
“… 1 It was found that the prevalence of GBS did not increase during the pandemic compared with previous years but that the outcome of SARS‐CoV‐2‐related GBS was worse compared with non‐COVID‐related GBS. 1 The study is appealing but carries limitations that raise concerns and should be discussed.…”
mentioning
confidence: 92%
See 3 more Smart Citations